Pedunculated focal nodular hyperplasia: a case report, case series, and in-depth surgical, radiological, and histological analysis of a rare phenomenon - Taylor Strange; Joseph M. Gosnell; Peeyush Bhargava; Abdulrahman Al Harbi; Luca Cicalese; Heather L. Stevenson (Diagnostic Pathology)
Abstract Background Focal nodular hyperplasia (FNH) is a benign hepatic lesion that rarely presents as an exophytic mass attached by a fibrous stalk (termed pedunculated FNH). This variation poses a challenge to clinicians, with atypical symptoms and imaging. Case presentation We describe a 33-year-old female who underwent excision of a pedunculated FNH. On gross examination, the lesion was lobular and vascular with homogenous tan-brown surfaces. Histological examination showed loss of normal liver architecture, abnormal intervening fibrous tracts, dysplastic arteries, and focal steatosis. Immunohistochemical staining with glutamine synthetase resulted in a branching, or “map-like” pattern. These findings were consistent with focal nodular hyperplasia. One of the most sensitive imaging techniques for diagnosing this lesion involves magnetic resonance imaging (MRI) with contrast, which discloses a homogenous mass that is hyperintense during the arterial phase with gradual decrease in intensity during the venous and equilibrium phases. The central stellate scar will often remain hyperintense for a prolonged period of time. On histology, normal hepatic architecture is lost to abnormal fibrotic bands and a characteristic stellate scar. Immunohistochemistry with glutamine synthetase uniquely highlights a map-like pattern that is not seen in other liver lesions. Conclusions Due to its atypical presentation and increased risk of complications compared to its intrahepatic counterpart, pedunculated FNH brings unique challenges for diagnosis and therapy. Proper identification of pedunculated FNH is critical for appropriate treatment. Our case highlights the importance of radiological and histopathological studies to accurately identify this lesion, as well as the benefits of surgical removal to prevent serious complications.